PENERAPAN MODEL PEMBELAJARAN PROJECT BASED LEARNING UNTUK MENINGKATKAN MOTIVASI DAN HASIL BELAJAR PESERTA DIDIK PADA MATERI HAK DAN KEWAJIBAN DI KELAS IV SD NEGERI MELAYU MUHAMMADIYAH MAKASSAR - Amanda Sri Noviyanti; A. Nurul Ainun (Didaktik : Jurnal Ilmiah PGSD STKIP Subang, 2024)
Low student motivation to learn is not uncommon in the learning process. Low learning motivation is one of the causes of low student learning outcomes. The aim of this classroom action research was to increase student motivation and learning outcomes by applying the Project Based Learning learning model to the material on rights and obligations in class IV of SD Negeri Melayu Muhammadiyah Makassar. The subjects of this research were all class IV students at SD Negeri Melayu Muhammadiyah Makassar with a total of 22 people for the 2024/2025 academic year. The data collection technique used in this research uses observation sheets and interviews to obtain data related to student motivation. To determine student learning outcomes, a post-test sheet in the form of an LKPD is used. The application of the Project Based Learning learning model to learning with material on rights and obligations has an influence on increasing student motivation and learning outcomes. In cycle I, the average learning motivation of students was 70.59. These students' learning motivation increased in cycle II with an average of 82.95. Student learning outcomes in cycle I reached an average of 75.86. These students' learning outcomes increased in cycle II with an average of 88.36. Therefore, this research has succeeded in achieving all indicators of success and this research includes two learning cycles.